Effect of Group Guidance with Self-Affirmation on Students’ Body Image Dissatisfaction - Nakita Augydia Lesmana; Nefi Darmayanti (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Body image dissatisfaction is a significant issue affecting adolescents’ mental health, including lowered self-esteem and increased anxiety. This study aimed to examine the effectiveness of group guidance using the self-affirmation technique in reducing body image dissatisfaction among ninth-grade students at MTsS Mandurana Tanjung Botung, Padang Lawas Regency. A quantitative approach with a one-group pretest-posttest design was employed. Eight students were selected purposively based on high to very high levels of body image dissatisfaction. The intervention consisted of four group guidance sessions using self-affirmation techniques over two weeks. Data were collected using a validated body image dissatisfaction scale and analysed using the Wilcoxon Signed Rank Test with SPSS 26. The results showed that prior to the intervention, 88% of students were in the very high category and 12% in the high category. After the intervention, all students (100%) fell into the very low category. Statistical analysis indicated a significance value of 0.012 (<0.05) with an effect size of -0.89, categorised as large, indicating a very strong impact. In conclusion, group guidance with the self-affirmation technique is effective in reducing adolescents’ body image dissatisfaction and can be applied in school counselling services. This study provides a basis for developing psychological interventions for adolescents that integrate group support and self-affirmation.